Urbanization in the Central and Eastern Visayas - Abenoja, Macrina Kilaton 1950- (1975)
Abstract

Past hierarchy studies have unanimously observed more advanced
settlements to be successively fewer than the less developed areas. Available municipal data in two central Philippine regions and the employment of scalogram analysis, however, demonstrate that middle ranking municipalities are more predominant than the high and low ranking towns. These dissimilarly developed towns spatially interrelate in a manner whereby the relatively underdeveloped towns avail themselves of the more complex services present in the more developed towns but which are wanting in these emerging localities.
The same municipal data display the double orientation of Philippine
migration, as observed by previous researches, in a certain peculiar way.
Movements towards the more developed areas predominate migration into the region, while the rural trend is prevalent in cases of movements out of the region.
This study identifies the two Visayan regions as areas of outmigration – a
confirmation of previous finding. It also reveals some popular migration- differential findings, like young males tend to be the most mobile segment of the population. It also indicates a divergent manner by which mobility is effected by sex.
Thesis (M.A.)--University of the Philippines, Manila.
Keywords: Urbanization -- Visayas, Central; Rural-urban migration -- Philippines -- Visayas, Central; Rural-urban migration -- Philippines -- Visayas, Eastern; Urbanization -- Visayas, Eastern